ANALYSIS OF THE IMPACT OF SWEETED FOOD AND BEVERAGE CONSUMPTION ON INDONESIAN TEENAGERS. - Fajar Anasta Meylias Ginting; Arya Sari Harahap; Cinta Malikah Azzahra; Keiza Ardhelia Arzah; Cut Mutia Fazira (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2024)
Non-communicable diseases (NCDs) such as obesity, type II diabetes mellitus, and cardiovascular diseases are increasingly prevalent in Indonesia, particularly among adolescents. High consumption of sugary beverages significantly contributes to the prevalence of these NCDs. Obesity, often driven by excessive sugar intake, can lead to various physical and psychological health issues. Type II diabetes mellitus also shows a significant rise, with factors such as obesity and unhealthy lifestyle playing major roles. Cardiovascular diseases, closely linked to obesity and unhealthy eating patterns, are also on the rise. Factors like weak regulation, affordable prices, and aggressive marketing contribute to high sugary beverage consumption. Efforts to improve regulation, health education, and policy reform are essential to reduce excessive sugar intake and lower the prevalence of NCDs among adolescents.